Tinjauan Hukum Islam, Hukum Internasional dan Perundang-Undangan tentang Pelaku Lesbian, Gay, Biseks, dan Transgender (LGBT) - Abd. Raziq; Jumadil; Arsul Maddupe; Safaruddin (Al-Azhar Islamic Law Review, 2023)
This study aims to find out the views of Islamic law, international law, and legislation regarding the law of LGBT actors in the type of literature research using a normative juridical approach. The source of data used in this study is primary data collected by reading official documents such as the Al-Qur'an, Hadith, Fiqh, and national and international laws and regulations. Data collection techniques through documents such as the Al-Qur'an and Hadith as well as laws and regulations. The view of Islamic law towards LGBT is that the law is unlawful because it violates human nature, the punishment is the same as for adultery, although some scholars punish Ta'zir (submitted to the government). "According to international law, although many countries reject the existence of LGBT groups, PPB strictly stipulates positive laws for LGBT actors by providing protection for LGBT people for human rights reasons. The legislation regulates LGBT through the Criminal Code which was passed by the DPR on December 6, 2022, Article 414 and Article 411 concerning same-sex obscenity, Article 411 paragraph (1) has the potential to ensnare LGBT people. However, the criminal threat can only be applied if there are parties who complain or because this article like a complaint offense. The maximum penalty is one year's imprisonment. The Criminal Code does not provide criminal threats against lesbian, gay, bisexual, and transgender (LGBT) groups.